Case report: cerebral venous sinus thrombosis and pulmonary embolism as the initial presentation in a child with asymptomatic primary nephrotic syndrome - Wang, Qinhui; Cui, Yaru; Liang, Ping; Wang, Chuan; Zhou, Kaiyu; Ma, Fan; Duan, Hongyu (Frontiers in Pediatrics, 2023)
Background: Cerebral venous sinus thrombosis (CVST) is rare, but potentially life-threatening. The clinical course definitely become more unpredictable and fatal in patients complicated by pulmonary embolism (PE). Nephrotic syndrome (NS) is an uncommon etiology of CVST. Concurrence of CVST and PE at the initial onset of NS is extremely unusual and rarely reported. Considering that edema might be absent in NS individuals, thromboembolic events probably become unrecognized, thereby causing a missed or delayed diagnosis and poor outcome. Herein, we described an extraordinary case of an adolescent boy presenting with both CVST and PE initially just within five days of disease onset, who was ultimately diagnosed with asymptomatic NS, aiming to emphasize a high index of suspicion of these diseases in patients with conditions of hypercoagulability. Case presentation: A 13-year-old male child presented acutely with dizziness, fever and dyspnea, with signs of shock but undetected edema. Initial laboratory investigations revealed hypoalbuminemia, typical images of pneumonia, and normal radiographic findings on non-enhanced computed tomography of head. Despite evidence of hypoalbuminemia and neurological symptoms, the child was still misdiagnosed as pneumonia. His dyspnea and period of headache deteriorated even if hemodynamic stability and undetected fever after initial therapy. The delayed urinalysis and 24-h urine examination both showed massive proteinuria. A computed tomography angiography of chest along with cranial magnetic resonance imaging/magnetic resonance venography were subsequently performed, consistent with the imaging features of PE and CVST, respectively. The diagnosis of asymptomatic primary NS complicated by PE and CVST was ultimately confirmed. The patient received corticosteroids and antithrombotic therapy with satisfactory results. Conclusions: A persistent clinical suspicion of CVST should be borne in mind in patients with a sudden, new or worsening headache, specifically among those with prothrombotic conditions. NS should always be considered in the differential diagnosis of risk factors for CVST, even in absence of edema. Since CVST and PE can be present simultaneously at extraordinary early-onset of NS, early radiological diagnosis is clinically substantial to proper management and satisfactory long-term outcomes.